Conservative management of intracranial extradural haematoma presenting late. Issue 6 (June 1983) - Illingworth, R; Shawdon, H
Abstract : Three patients with intracranial extradural haematomas presenting several days after injury have been managed without surgery, with clinical improvement. Spontaneous resolution of the haematomas has been demonstrated by serial computed tomography over periods of six weeks.